Visual Representation in Sustainability Reports: Impact on Public Perception of Corporate Social and Environmental Reputation - Adi Pratama, I Wayan Bayu; Ardiana, Putu Agus (E-Jurnal Akuntansi; Vol 34 No 10 (2024)DO - 10.24843/EJA.2024.v34.i10.p03, 2024)
This study investigates the impact of visual representations in sustainability reports on public perceptions of corporate social and environmental reputations. The research focuses on 270 companies listed on the Indonesia Stock Exchange in 2022 and analyzes 563 sustainability reports published between 2020 and 2022 using content analysis methods. The content analysis aims to quantify the use of visual elements, such as images, photos, graphs, and tables, in these reports. Impression management theory is employed to interpret the findings. Logistic regression analysis is used to assess the data. The results indicate that visual representations significantly influence public perceptions of corporate social and environmental reputations. These visual elements enable companies to more effectively convey their sustainability efforts, achievements, and commitments to the public, thereby enhancing their reputation and trustworthiness.